Aspirasi Pemuda Kelas Bawah dan Reproduksi Sosial Di Jawa Tengah - Oki Rahadianto Sutopo; Rani Dwi Putri; Karin Larasati Kusumawardhani (Universitas Gadjah Mada, 2018)
Central Java is one of provinces that is progressive in developing its industries, especially in manufacturing. However, the unemployment rate among youth in this province turns out to be considerably high. The high number of unemployment rates and low participation in the labor market among youth are caused by various factors. One of them is the gap between human resources and demand in the labor market. The gap in education, skills, and access to information triggering the condition whereas youth are not counted to involve in the labor market. This gap certainly emerged based on the social class differences inherent in each young people. In addition, gender differences also affect opportunities and freedom in choosing a job. This research uses qualitative methods with the process of observation, in-depth interviews, and Focus Group Discussion as techniques for data collecting. Through the selection of two female and two male informants (purposive sampling), this research concludes that social class factors, gender, and changing contexts, especially in the conditions of Labor Market Flexibility (LMF) became the main factors in shaping and influencing the transition process related to future aspirations of youth. The application of neoliberalism and Labor Market Flexibility perpetuates the social reproduction based on class and gender which enables social gaps to increase in the future. This condition is predicted to marginalize poor and vulnerable young people even more